Getting Back to Work: Cognitive Behavioral Predictors of Depressive Symptoms and Job Search Success. Issue 6 (15th March 2016) - Pfeifer, Benjamin J.; Strunk, Daniel R.
Abstract : Objective: Little is known about how cognitive behavioral approaches to depression might explain functional impairments associated with the disorder, such as extended periods of unemployment. To address this issue, we examined 5 cognitive behavioral predictors of depressive symptom change and job search outcome. Method: Using a sample of 75 unemployed adults, we examined cognitive style, brooding, dysfunctional attitudes, avoidance, and cognitive behavioral (CB) skills as predictors of change in depressive symptoms, job search self‐efficacy, and receipt of a job offer over a 3‐month period. Results: CB skills predicted lower depressive symptoms and increased odds of having received a job offer at the follow‐up. Brooding predicted change in job search self‐efficacy, but not in the expected direction. Conclusion: CB skills appear to predict job search outcomes as well as depressive symptoms. We encourage future work examining how CB skills may affect depressive symptoms, job search behaviors, and other areas of functioning.